IMPLEMENTASI MODEL PEMBELAJARAN STORY BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA DI SEKOLAH DASAR - Trisnawati; Lusi Marleni; M. Syahrul Rizal; Mufarizuddin; Putri Hana Febriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was triggered by the low speaking skills of students in the Indonesian language subject of grade IV of Permata Topaz Elementary School which is characterized by a lack of courage to express opinions, limited use of vocabulary, and inappropriate pronunciation and intonation. One solution to overcome this problem is to use the Story Based Learning learning model. This research aims to improve students' speaking skills in the Indonesian language subject with fairy tales. The research method is Classroom Action Research (CAR) which is implemented in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The research time was carried out in November 2025. Data collection techniques include documentation, observation, and tests. The subjects of this study were 26 fourth-grade students, consisting of 12 male students and 14 female students. The data analysis techniques in this study were descriptive qualitative and quantitative. The results of this study showed an increase in students' speaking skills during the pre-action of 34.61%, then in cycle I meeting I increased to 50%, and cycle I meeting II increased to 65.38%. Furthermore, in cycle II meeting I increased to 80.76%, and cycle II meeting II increased to 88.46%. Thus, it can be concluded that using the Story Based Learning learning model can improve students' speaking skills in Indonesian language learning in grade IV of Permata Topaz Elementary School.